An Annotated Translation of a Book Entitled Experiencing God in The Ordinary - Marcella Evelyn; Julia Eka Rini (Institute of Research and Community Outreach - Petra Christian University, 2022)
An annotated translation is based on notes and observations which the translator writes down in the process of translation, concentrating mainly on problematic passages or passages with interesting features relating to the topic of the project. In this project, the author translated a 215-page book entitled Experiencing God in The Ordinary from English as the source language (SL )to Bahasa Indonesia as the target language (TL) using the annotated translation method. Based on the translation result, she classified and explained the difficulties encountered by using Newmark’s four levels in translation: the textual, the referential, the cohesive, and the naturalness.